Exfoliative diseases of the integument and mucous membrane that mimic deep 2nd-degree burns with or without sepsis - K Mathangi Ramakrishnan; Bala Ramachandran; K G Ravikumar; K Ravikumar; R Ramkumar; V Jayaraman; T Mathivanan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Exfoliative skin diseases in children can mimic burns in many ways and require early diagnosis and management. Here we enumerate the different skin conditions with four case based examples and their management. Clinical Presentation: Varying degrees of skin involvement may be seen with severe involvement in DRESS syndrome and milder involvement in Stevens-Johnson syndrome. Management: The management of this exfoliative lesion is the application of collagen membrane to the wound as we treat burns. Although systemic symptoms can produce mortality (e.g., dress), collagen dressing heals the wound well with good epithelialization. Early and appropriate antibiotic therapy is mandatory. Conclusion: Careful attention to correct diagnosis, early intervention and use of collagen dressing have improved outcome in these children.